HM and THM interactions in bentonite engineered barriers for nuclear waste disposal. (January 2021) - Gens, Antonio; Alcoverro, Jordi; Blaheta, Radim; Hasal, Martin; Michalec, Zdeněk; Takayama, Yusuke; Lee, Changsoo; Lee, Jaewon; Kim, Geon Young; Kuo, Chia-Wei; Kuo, Wan-Jung; Lin, Chung-Yi
Abstract: Bentonite-based engineered barriers are a key component of many repository designs for the confinement of high-level radioactive waste and spent fuel. Given the complexity and interaction of the phenomena affecting the barrier, coupled hydro-mechanical (HM) and thermo-hydro-mechanical (THM) numerical analyses are a potentially useful tool for a better understanding of their behaviour. In this context, a Task (INBEB) was undertaken to study, using numerical analyses, the hydro-mechanical and thermo-hydro-mechanical Interactions in Bentonite Engineered Barriers within the international cooperative project DECOVALEX 2019. Two large scale tests, largely complementary, were selected for modelling: EB and FEBEX. The EB experiment was carried out under isothermal conditions and artificial hydration and it was dismantled after 10.7 years. The FEBEX test was a temperature-controlled non-isothermal test combined with natural hydration that underwent two dismantling operations, a partial one after 5 years of heating and a final one after a total of 18.4 years of heating. Direct observation of the state of the barriers was possible during the dismantling operations so that the evolution of barrier heterogeneity under transient conditions could be determined. Four teams performed the HM and THM numerical analyses using a variety of computer codes, formulations and constitutive laws. For each experiment, the basic features of the analyses are described and the comparison between calculations and field observations are presented and discussed. Comparisons involve measurements performed during the performance of the test and data gathered during dismantling. A final evaluation of the performance of the modelling closes the paper. Highlights: Reports the DECOVALEX 2019 Task (INBEB) performed to study the HM and THM interactions in bentonite engineered barriers. Bentonite engineered barriers are a key component of deep geological repositories for high level nuclear waste. TH and THM coupled numerical analyses of two large scale tests (EB and FEBEX) are performed by four modelling teams. Simulation results are compared with field observations from the performance of the tests and dismantling operations. The performance of the various modelling approaches in relation to the observed barrier behavior is evaluated and discussed.